Combined alcohol septal ablation and transcatheter aortic valve replacement: Drunk and playing with fire. Issue 4 (11th March 2020) - Rowin, Ethan J.; Kimmelstiel, Carey
Key Points: Evaluation of the severity of aortic stenosis in the presence of dynamic left ventricular outflow (LVOT) obstruction is challenging. Invasive hemodynamic assessment with provocative maneuvers can be useful to differentiate of the relative components of obstruction. In patients with both dynamic LVOT obstruction and aortic stenosis, surgical myectomy and concurrent surgical aortic valve replacement is the optimal treatment strategy; combined alcohol septal ablation and transcatheter aortic valve replacement should only be considered for very high surgical risk patients.